Source apportionment of airborne nanoparticles in a Middle Eastern city using positive matrix factorization. Issue 4 (6th March 2015) - Al-Dabbous, Abdullah N.; Kumar, Prashant
Abstract : Airborne nanoparticles have been studied worldwide, but little is known about their sources in the Middle East region, where hot, arid and dusty climatic conditions generally prevail. Abstract : Airborne nanoparticles have been studied worldwide, but little is known about their sources in the Middle East region, where hot, arid and dusty climatic conditions generally prevail. For the first time in Kuwait, we carried out size-resolved measurements of particle number distributions (PNDs) and concentrations (PNCs) in the 5–1000 nm size range. Measurements were made continuously for 31 days during the summer months of May and June 2013 using a fast-response differential mobility spectrometer (Cambustion DMS500) at a sampling rate of 10 Hz. Sources and their contributions were identified using the positive matrix factorization (PMF) approach that was applied to the PND data. Simultaneous measurements of gaseous pollutants ( i.e., O3, NO, NO x, SO2 and CO), PM10, wind speed and direction were also carried out to aid the interpretation of the PMF results through the conditional probability function plots and Pearson product–moment correlations. Six major sources of PNCs were identified, contributing ∼46% (fresh traffic emissions), 27% (aged traffic emissions), 9% (industrial emissions), 9% (regional background), 6% (miscellaneous sources) and 3% (Arabian dust transport) of the total PNCs. The sources of nanoparticles and their PND profiles identified could serve as reference data to design more detailed field studies in the future and treat these sources in dispersion modelling and health impact assessment studies.